2015
DOI: 10.1038/bjc.2015.240
|View full text |Cite
|
Sign up to set email alerts
|

Serum GADD45a methylation is a useful biomarker to distinguish benign vs malignant prostate disease

Abstract: Background:Prostate-specific antigen (PSA) screening for prostate cancer results in a large number of unnecessary prostate biopsies. There is a need for specific molecular markers that can be used in combination with PSA to improve the specificity of PSA screening. We examined GADD45a methylation in blood DNA as a molecular marker for prostate cancer diagnosis.Methods:The study included 82 men, with PSA levels >4 ng ml−1 and/or abnormal digital rectal exam, who underwent prostate biopsy. We compared GADD45a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 43 publications
0
40
0
Order By: Relevance
“…They are engaged in regulating of intrinsic apoptotic pathways. Previous studies on different human cancers have analysed and confirmed the DNA methylation changes in these genes, but none of them were demonstrated these changes in EC San Jose-Eneriz et al 2009;Perugini et al 2013;Cho et al 2014;Kucuk et al 2015;Reis et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are engaged in regulating of intrinsic apoptotic pathways. Previous studies on different human cancers have analysed and confirmed the DNA methylation changes in these genes, but none of them were demonstrated these changes in EC San Jose-Eneriz et al 2009;Perugini et al 2013;Cho et al 2014;Kucuk et al 2015;Reis et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of GADD45A causes dissociation of BIM from the microtubule-associated components and translocation to mitochondria (Tong et al 2005). So far increased DNA methylation level in promoter region of GADD45A gene was observed in breast, prostate cancer and acute myeloid leukemia where it is associated with decreased expression level, poor prognosis a might be useful as marker to distinguish benign vs. malignant solid tumors (Perugini et al 2013;Reis et al 2015). These result are inconsistent with ours, thus we can only suggest that methylation of GADD45A gene can be included in EEC-L development.…”
Section: Discussionmentioning
confidence: 99%
“…GADD45a methylation in prostate cancer plasma is apparently higher than in benign prostate tumor plasma [84]. Other circulating methylation markers include SESN3 [82], WIF1, and NPY [85] for localized colorectal cancer, RAS [86], PTK2, WIF1, and NPY [85] for metastatic colorectal cancer, TAC1 [87] promoter for esophageal adenocarcinoma, RASSF1A [81] for thyroid cancer, SEPT9 [88] for hepatocellular carcinoma, and SHOX2 and SEPT9 [89] for head and neck squamous cell carcinomas.…”
Section: Ctdna and Chromatin Modificationmentioning
confidence: 99%
“…Previous studies have identified an array of genes subjected to methylation-dependent transcriptional silencing in melanoma. Furthermore, detection of methylated genomic DNA in peripheral blood is an attractive potential source of cancer biomarkers because of the stability of DNA and the relative specificity of methylation for malignant disease (14). The requirement for sensitive and specific biomarkers of recurrent and particularly unresectable/metastatic melanoma has been emphasised by…”
Section: {Page } Introductionmentioning
confidence: 99%